Structural and Optoelectronic Properties of Two-Dimensional Ruddlesden–Popper Hybrid Perovskite CsSnBr3 - Guangbiao Xiang; Yanwen Wu; Yushuang Li; Chen Cheng; Jiancai Leng; Hong Ma (Nanomaterials, 2021)
Ultrathin inorganic halogenated perovskites have attracted attention owing to their excellent photoelectric properties. In this work, we designed two types of Ruddlesden–Popper hybrid perovskites, Csn+1SnnBr3n+1 and CsnSnn+1Br3n+2, and studied their band structures and band gaps as a function of the number of layers (n = 1–5). The calculation results show that Csn+1SnnBr3n+1 has a direct bandgap while the bandgap of CsnSnn+1Br3n+2 can be altered from indirect to direct, induced by the 5p-Sn state. As the layers increased from 1 to 5, the bandgap energies of Csn+1SnnBr3n+1 and CsnSnn+1Br3n+2 decreased from 1.209 to 0.797 eV and 1.310 to 1.013 eV, respectively. In addition, the optical absorption of Csn+1SnnBr3n+1 and CsnSnn+1Br3n+2 was blue-shifted as the structure changed from bulk to nanolayer. Compared with that of Csn+1SnnBr3n+1, the optical absorption of CsnSnn+1Br3n+2 was sensitive to the layers along the z direction, which exhibited anisotropy induced by the SnBr2-terminated surface.